2021
DOI: 10.1186/s12883-021-02268-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between tirofiban monotherapy and efficacy and safety in acute ischemic stroke

Abstract: Background Studies have suggested that glycoprotein IIb/IIIa antagonists such as tirofiban are beneficial for patients with acute coronary syndromes. However, it is still uncertain about the efficacy and safety of tirofiban in patients with acute ischemic stroke (AIS). Methods In this prospective non-randomized study, 255 AIS patients were recruited from 4 comprehensive stroke centers in China between January, 2017 and May, 2018. Among them,169 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Torgano et al reported that the functional outcome at 90 days, mortality and symptomatic intracranial hemorrhage were comparable between tiro ban and aspirin group [23]. In the study of Tao et al, tiro ban alone was noninferior to DAPT with regard to 90-day mRS [24], while another study by Wang et al showed that tiro ban performed better than DAPT in 90-day mRS and the occurrence of END [25]. The e cacy of tiro ban in AIS remains to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…Torgano et al reported that the functional outcome at 90 days, mortality and symptomatic intracranial hemorrhage were comparable between tiro ban and aspirin group [23]. In the study of Tao et al, tiro ban alone was noninferior to DAPT with regard to 90-day mRS [24], while another study by Wang et al showed that tiro ban performed better than DAPT in 90-day mRS and the occurrence of END [25]. The e cacy of tiro ban in AIS remains to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…The SaTIS (Safety of Tirofiban in Acute Ischemic Stroke) trial showed that tirofiban alone did not increase the risk of cerebral infarction hemorrhage or parenchymal hemorrhage and significantly reduced mortality rates [22]. Tirofiban could reduce the rate of ICH and mortality even when compared with standard dual antiplatelet therapy [23].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous recombination tissue plasminogen activator (rt‐PA) has been widely recommended as a standard treatment for acute ischemic stroke (AIS) in most clinical practice guidelines 2 . However, only about 5%–20% of AIS patients received rt‐PA treatment, which is restricted by the narrow therapeutic time window, and only 2% of stroke patients could be beneficial from this treatment regimen 3,4 . Endovascular intervention can restore blood flow promptly, and thrombectomy with stent retrievers is now recommended as the standard care for AIS with a proximal large vessel occlusion (LVO) 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 However, only about 5%–20% of AIS patients received rt‐PA treatment, which is restricted by the narrow therapeutic time window, and only 2% of stroke patients could be beneficial from this treatment regimen. 3 , 4 Endovascular intervention can restore blood flow promptly, and thrombectomy with stent retrievers is now recommended as the standard care for AIS with a proximal large vessel occlusion (LVO). 5 , 6 However, as inherent damage to the endothelial cells lining of a blood vessel, endovascular treatment (EVT), such as mechanical thrombectomy (MT), angioplasty, and stenting, lead to local platelet aggregation, contributing to subsequent early reocclusion and thromboembolic complications.…”
Section: Introductionmentioning
confidence: 99%